Enhanced Osteogenesis and Antibacterial Properties of Ketoprofen-Loaded MgCu-MOF74-Coated Titanium Alloy for Bone Implant - Ziqing Duan; Yifeng Yao; Jiamin Liu; Yanni Tan; Qingge Wang; Man Fang; Aqsa Kanwal; Shuqiao Cheng; Juan Huang; Hong Wu (Journal of Functional Biomaterials)
To address the dual clinical challenges of poor osseointegration and inadequate analgesia caused by postoperative infections in traditional titanium implants, this study proposes a multifunctional synergistic strategy based on metal—organic frameworks (MOFs). By integrating drug-controlled release and ionic microenvironment regulation, it constructs a titanium-based implant coating system with antibacterial and bone-regenerative properties. Ketoprofen, a drug with excellent analgesic properties, was loaded into MgCu-MOF74 powder, and the Ket@MgCu-MOF74 powder was successfully anchored onto the surface of the titanium alloy through dopamine-mediated adhesion. The maximum load of ketoprofen to MgCu-MOF74 is 18.55%, and it has a good controllable release effect. The results showed that MgCu-MOF74/Ti and Ket@MgCu-MOF74/Ti coatings enhanced osteogenic performance by promoting alkaline phosphatase activity, collagen secretion, and extracellular matrix mineralization. Additionally, the release of Mg2+ and Cu2+ created an alkaline environment, providing antibacterial properties. In summary, the MOF enabled the controlled release of ketoprofen, and the composite coating can improve osteogenic differentiation of osteoblasts and enhance the antibacterial properties of titanium alloy implants.